2020
DOI: 10.3390/ijerph18010001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Indicators of Vitamin B12 Insufficiency among Young Women of Childbearing Age

Abstract: Vitamin B12 insufficiency is a global health issue among women of childbearing age, yet few studies have investigated its prevalence and risk factors among healthy Middle Eastern populations. This cross-sectional study included 346 Saudi women aged 19–30 years and enrolled at King Saud University, Riyadh, Saudi Arabia. A series of questionnaires were administered to record the study participants’ sociodemographic status, medical history, dietary intake, and physical activity. Participants’ anthropometric data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…While considerable attention has been given to the macronutrient–gut microbiota relationship [ 9 ], studies have rarely focused on the role of vitamins (e.g., vitamin B12) [ 10 , 11 ]. Vitamin B12 insufficiency (<200 pmol/L) is a common condition worldwide [ 12 ], reaching an incidence of 10.6% in the United States [ 13 ] and 6% in Saudi females of reproductive age (≤220 pmol/L) [ 14 ]. Vitamin B12 insufficiency has been linked to a variety of health problems, ranging from minor tiredness and megaloblastic anemia to severe neurological damage [ 12 ], as well as the development of metabolic diseases, particularly obesity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…While considerable attention has been given to the macronutrient–gut microbiota relationship [ 9 ], studies have rarely focused on the role of vitamins (e.g., vitamin B12) [ 10 , 11 ]. Vitamin B12 insufficiency (<200 pmol/L) is a common condition worldwide [ 12 ], reaching an incidence of 10.6% in the United States [ 13 ] and 6% in Saudi females of reproductive age (≤220 pmol/L) [ 14 ]. Vitamin B12 insufficiency has been linked to a variety of health problems, ranging from minor tiredness and megaloblastic anemia to severe neurological damage [ 12 ], as well as the development of metabolic diseases, particularly obesity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that a higher maternal dietary intake of vitamin B12 improved certain infant neurocognitive abilities, regardless of vitamin B12 levels. This may be because serum vitamin B12 levels are a late marker of intake and therefore do not reflect the current intake [ 66 , 67 ], as was reported in a systematic review with dose–response meta-analyses of vitamin B12 intake and biomarkers [ 68 ] and in a previous study by our research group [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was the lack of additional vitamin B12 biomarkers, such as homocysteine, to improve the evaluation of vitamin status. Since the determination of serum vitamin B12 reflects late deficiency, its combination with another marker such as methylmalonic acid or holotranscobalamin, which are early markers of deficiency, could help to broaden the evaluation of vitamin status [ 66 , 67 ]. Moreover, we did not assess genetic variants related to vitamin B12 metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This study has various strengths based on several aspects. First, the original design of the study was a triple-blind, population-based RCT (Arija et al, 2014), providing a high level of scientific rigour and on the participants' vitamin B12 levels (Al-Musharaf, et al, 2020;Obeid et al, 2019). Serum vitamin B12 levels were also not measured in the pre-school-aged children at the time of the psychological evaluation.…”
Section: Discussionmentioning
confidence: 99%